1955
DOI: 10.1071/bi9550137
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of Pea Fruits I. the Developing Fruit

Abstract: Pea fruits from two crops were sampled at different times from flowering. Changes in the fresh weight, dry weight, starch, soluble carbohydrate, protein nitrogen, and soluble nitrogen in both seeds and hulls were followed in two seasons and related Jo the changes in cell volume in the seeds. In one season respiration rates and phosphate, pectin, and ascorbic acid contents were also investigated. The seeds gained more carbohydrate and nitrogen than was lost by the hulls. Starch and protein were synthesized rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
31
1

Year Published

1957
1957
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 11 publications
6
31
1
Order By: Relevance
“…No account was taken of the possibility of other sources of nutrition for normally maturing seeds in these studies on detached fruits. Later studies (4,16,17) of pea fruit development on the plant came to similar conclusions from examination of changes in various soluble and insoluble biochemical fractions during hull and seed development. The evidence here was of a correlative nature based partly on consideration of the different timing of pod and seed maturation.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…No account was taken of the possibility of other sources of nutrition for normally maturing seeds in these studies on detached fruits. Later studies (4,16,17) of pea fruit development on the plant came to similar conclusions from examination of changes in various soluble and insoluble biochemical fractions during hull and seed development. The evidence here was of a correlative nature based partly on consideration of the different timing of pod and seed maturation.…”
mentioning
confidence: 61%
“…Early this century it was suggested that reserves deposited in legume pods might be a source of nutrition for their enclosed developing seeds (7, 23, 30; reviewed in 17). A transfer of reserves of C or N was assumed from observation of losses by pods and gains by seeds.…”
mentioning
confidence: 99%
“…In Glycine max the proteins appear after the starch grains (Bils and Howell 1963) although a few grains, called ribonucleoproteins (Stephenson et al 1959), are present earlier. Most authors (Bisson and Jones 1932, McKee et al 1955, Bain and Mercer 1966 working on peas have observed a close similarity in the time of initiation and duration of protein and starch synthesis. The observations on the cotyledons of C. cajan and V. radiata (present work) agree with the above statement.…”
Section: Discussionmentioning
confidence: 99%
“…Although they made good use of the methodology then available, these studies from a present-day point of view are inadequate in several ways: either the results were only semiquantitative (17,22), or sampling was very infrequent or did not cover the whole span of development (8,12,22), or many amino acids were omitted altogether (8,12,17,22). Conspicuous among the latter are the sulfur amino acids; where cysteine was determined, no precautions were taken to prevent oxidative losses.…”
mentioning
confidence: 99%
“…Developmental changes in free amino acid levels have been investigated in Pisum sativum (17), P. arvense (8), three species of Lathyrus (22), and Glycine max (12). Although they made good use of the methodology then available, these studies from a present-day point of view are inadequate in several ways: either the results were only semiquantitative (17,22), or sampling was very infrequent or did not cover the whole span of development (8,12,22), or many amino acids were omitted altogether (8,12,17,22).…”
mentioning
confidence: 99%